Analysis of the Application of Management of Patient Safety and Housekeeping in the Prevention of Fall Patients - Barlianto Nugroho (Journal for Quality in Public Health, 2020)
Patient safety becomes a global and national issue because Patient Safety is important in order to minimize risks and errors in health service areas in Puskesmas. The purpose of this study is to Analyze the application of patient safety management and housekeeping in efforts to prevent falling patients in UPTD Puskesmas Puhjarak, Pl Kediri. The design of this study is to use a qualitative method using a phenomenological approach which is a type of qualitative research that looks closely at individual interpretations of their experiences. Data collection techniques used are Participant observational, independent interview, documentation and triangulation. Research instruments: Researchers as instruments (human instruments), notebooks, tape recorders, cameras. Data: qualitative descriptive, personal data documents, field notes, statements and actions of informants, documents etc. with a sample size of 10 informants who are officers in each service unit in the health center puhjarak. Data verification with Triangulation Techniques was conducted by 2 informants. Research results this shows that the application of patient safety seen from the leadership of the head of the puskesmas that is, has delegated authority well, but regarding giving awards and strict sanctions against employees has never been done. quickly get a positive response because there is a process of completion stages. Workload for employees is very much concurrent with programs and activities outside the building so that they do not have free time to apply patient safety. Knowledge / skills for the head of the Puhjarak Community Health Center and the Head of PMKP patient while the employee has never been. Researcher Suggestion is expected that Puskesmas Puhjarak creates a comfortable working atmosphere for employees and looks for solutions to patient safety problems